Effectiveness of Influenza Vaccination in Preventing Hospitalization Due to Influenza in Children: A Systematic Review and Meta-analysis. (27th March 2021) - Boddington, Nicki L; Pearson, Isabelle; Whitaker, Heather; Mangtani, Punam; Pebody, Richard G
Abstract: This systematic review assesses the literature for estimates of influenza vaccine effectiveness (IVE) against laboratory-confirmed influenza-associated hospitalization in children. Studies of any design to June 8, 2020, were included if the outcome was hospitalization, participants were 17 years or younger and influenza infection was laboratory-confirmed. A random-effects meta-analysis of 37 studies that used a test-negative design gave a pooled seasonal IVE against hospitalization of 53.3% (47.2–58.8) for any influenza. IVE was higher against influenza A/H1N1pdm09 (68.7%, 56.9–77.2) and lowest against influenza A/H3N2 (35.8%, 23.4–46.3). Estimates by vaccine type ranged from 44.3% (30.1–55.7) for live-attenuated influenza vaccines to 68.9% (53.6–79.2) for inactivated vaccines. IVE estimates were higher in seasons when the circulating influenza strains were antigenically matched to vaccine strains (59.3%, 48.3–68.0). Influenza vaccination gives moderate overall protection against influenza-associated hospitalization in children supporting annual vaccination. IVE varies by influenza subtype and vaccine type. Abstract : This study provides a complete and up-to-date review of the literature and highlights that influenza vaccination provides good protection against any influenza-associated hospitalisation in children and provides continued support for annual vaccination in children. Effectiveness varies by subtype and vaccine type.